A Novel Biomarker‐Based Approach for the Detection of Asymptomatic Brain Injury During Catheter Ablation of Atrial Fibrillation. (4th December 2013) - SRAMKO, MAREK; PEICHL, PETR; WICHTERLE, DAN; TINTERA, JAROSLAV; MAXIAN, RADOSLAV; WEICHET, JIRI; KNESPLOVA, LENKA; FRANEKOVA, JANKA; PASNISINOVA, SILVIA; KAUTZNER, JOSEF
<x xml:space="preserve">Abstract</x> Background Diffusion‐weighted magnetic resonance imaging (DW‐MRI) is a widely used method for studying of asymptomatic brain injury during catheter ablation of atrial fibrillation (AF). However, this technique lacks sensitivity for subtle or diffuse brain lesions. We investigated whether detection of the ablation‐related brain injury can improve by assessment of a biomarker of brain damage—protein S100B. Methods and Results DW‐MRI and assessment of S100B were performed in 58 patients undergoing radiofrequency catheter ablation of paroxysmal or persistent AF 1 day before and after the procedure. We observed no symptomatic neurological complications. S100B levels increased after ablation above the upper reference limit of 105 ng/L in 3 patients. One of them developed a new ischemic lesion on the DW‐MRI. No acute lesions emerged on DW‐MRI in the patients with normal postablation S100B levels. Conclusion Serial assessment of serum protein S100B may improve detection of asymptomatic acute brain injury in patients undergoing radiofrequency catheter ablation of AF. In our study, the incidence of these events was 1.7% when evaluated only by DW‐MRI, but the incidence increased to 5% after employing the more sensitive biomarker‐based approach.